PLATELET TO LYMPHOCYTE RATIO IN THE HEALTHY POPULATION OF VOJVODINA: PLATELET TO LYMPHOCYTE RATIO IN THE HEALTHY POPULATION - Šašić Ostojić, Tanja (Journal of Medical Biochemistry, 2025)
BACKGROUND: Platelet to lymphocyte ratio (PLR) is a simple laboratory index that may be applied in diagnostics and follow up the different diseases, with primary or accompanying systemic inflammatory component. However, due to lack of reference interval in general population, clinical application of PLR index is limited. The aim of this study was to determine the reference interval of PLR index.METHODS: Retrospective observational study included 4672 adult examinees, which underwent regular systematic check-up, including clinical examination and basic laboratory analyses (complete blood count-CBC). The PLR reference interval was calculated using the Clinical and Laboratory Standards Institute guidelines estimating percentiles and their 95% confidence intervals-CI). Verification of reference interval was performed on the group of 95 healthy adults, age and gender matched to the examined one. RESULTS: The mean age of all examinees was 43±10 years, dominantly males (83.7%). PLR median value was 109(25thpercentile:90-75thpercentile:131; lower limits of the median-62(95%CI:61-63); upper limits of the median-194(95%CI:188-198)). Female had significantly higher PLR levels compared to male (P0.05.CONCLUSIONS: In representative sample of examinees, where the majority was of young and middle age, PLR reference interval for women is 70-231, while for men is 61-183. In persons older than 65, the values of PLR index may be lower.
Keywords: Complete blood count, Laboratory testing, Platelet to lymphocyte ratio, Reference values